Weakness of will and delay discounting - Heinzelmann, Nora (Oxford scholarship online, 2023)
Both philosophy and the behavioural sciences have studied weakness of will and our propensity to discount the value of delayed outcomes. Nora Heinzelmann now brings the disciplines together, making the ideas of each accessible to the other. It reveals that delay discounting is neither necessary not sufficient for weakness of will.